Contribution Biopellets as Energy New Renewable from Stalks, Bunches, Waste, Fresh Fruit Bunches, and Shells Coconut (Cocos nucifera) - Brefty Meysi Afrilia F; Ingrid Ovie Yosephine; Giyanto (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
Indonesia is the world's largest producer of coconut palm oil, with a total production of 46,986,128 tons in 2023, cultivated over 16,833,985 hectares. This research aims to utilize waste from harvesting fresh fruit bunches (FFB) of coconut palm oil—specifically, bunch stalks and coconut shells—as raw materials for the manufacture of biopellets. Additionally, the study evaluates the influence of varying compositions on the quality characteristics of biopellets, including calorific value, moisture content, ash content, density, and combustion rate. The research employed an experimental method using a Completely Randomized Design (CRD) with a non-factorial arrangement. The treatments consisted of five composition levels of fresh fruit bunches to coconut shell ratios: 100% FFB: 0% shell (K1), 75%: 25% (K2), 50%: 50% (K3), 25%: 75% (K4), and 0%: 100% (K5). Each treatment was replicated three times. The study stages included raw material preparation, chopping, drying of TBS stalks, milling to a particle size of 30 mesh (<0.6 mm), mixing with coconut shell using an adhesive made from gaplek/tapioca flour, pelletizing, drying in an oven at 80°C for 1 hour, and subsequent quality testing according to research parameters. Results indicate that the proportion of coconut shell significantly affects the biopellet characteristics. The highest calorific value was observed in treatment K5 (100% shell) at 3,924.24 cal/g, while the lowest was in K1 (100% FFB) at 3,226.64 cal/g. All treatments met the SNI 8675:2018 standard for moisture content, with the lowest at 5.47% in K5 and the highest at 6.60% in K2. However, ash content across all treatments did not meet the SNI standard, ranging from 22.80% to 36.13%. Biopellet density met the standard, averaging 0.73 g/cm³, and the combustion rate also complied with the standard, averaging 0.00096 g/second. In conclusion, substituting coconut shell for fresh fruit bunch stalks increases the calorific value and improves several quality parameters of biopellets, with the best results observed in treatment K5 for calorific value and moisture content.